Biliary system architecture: experimental models and visualization techniques - Sarnova, L; Gregor, M (Physiological research, 2017)
The complex architecture of the liver biliary network represents a structural prerequisite for the formation and secretion of bile as well as excretion of toxic substances through bile ducts. Disorders of the biliary tract affect a significant portion of the worldwide population, often leading to cholestatic liver diseases. Cholestatic liver disease is a condition that results from an impairment of bile formation or bile flow to the gallbladder and duodenum. Cholestasis leads to dramatic changes in biliary tree architecture, worsening liver disease and systemic illness. Recent studies show that the prevalence of cholestatic liver diseases is increasing. The availability of well characterized animal models, as well as development of visualization approaches constitutes a critical asset to develop novel pathogenetic concepts and new treatment strategies.
Keywords: žlučové cesty; cholestáza; Disease Models, Animal; zobrazování trojrozměrné; modely nemocí na zvířatech; Microscopy, Electron, Scanning; teoretické modely; Models, Theoretical; Animals; lidé; Biliary Tract; mikroskopie elektronová rastrovací; Imaging, Three-Dimensional; Bile Ducts; zvířata; Humans; Cholestasis; žlučové ústrojí